2011
DOI: 10.1063/1.3531996
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the bandgap engineering of Al1−xGaxN for optoelectronic applications

Abstract: A theoretical study of Al 1−x Ga x N, based on the full-potential linearized augmented plane wave method, is used to investigate the variations in the bandgap, optical properties, and nonlinear behavior of the compound with the change in the Ga concentration. It is found that the bandgap decreases with the increase in Ga. A maximum value of 5.50 eV is determined for the bandgap of pure AlN, which reaches a minimum value of 3.0 eV when Al is completely replaced by Ga. The static index of refraction and dielectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Guerrero et al 23 carried out room temperature reflectivity measurements on MBE grown zb-Al An analysis of reported theoretical data reveals inconsistencies in the numerical description of the composition dependence of the fundamental zb-Al x Ga 1−x N band gaps as well. Recently, Amin et al 27 employed the Wu-Cohen generalized gradient approximation (GGA) within a full-potential linearized augmented plane wave approach (FLAPW) to calculate the zb-Al x Ga 1−x N band gaps over the entire composition range. Consistent with the band gap data of Okumura et al, the alloy band gap was found to be direct for the entire composition range, increasing linearly from a direct band gap of 3.00 eV in zb-GaN to a direct band gap of 5.50 eV in zb-AlN.…”
Section: Introductionmentioning
confidence: 99%
“…Guerrero et al 23 carried out room temperature reflectivity measurements on MBE grown zb-Al An analysis of reported theoretical data reveals inconsistencies in the numerical description of the composition dependence of the fundamental zb-Al x Ga 1−x N band gaps as well. Recently, Amin et al 27 employed the Wu-Cohen generalized gradient approximation (GGA) within a full-potential linearized augmented plane wave approach (FLAPW) to calculate the zb-Al x Ga 1−x N band gaps over the entire composition range. Consistent with the band gap data of Okumura et al, the alloy band gap was found to be direct for the entire composition range, increasing linearly from a direct band gap of 3.00 eV in zb-GaN to a direct band gap of 5.50 eV in zb-AlN.…”
Section: Introductionmentioning
confidence: 99%
“…The imaginary part of the dielectric function, ε 2 (ω), represents the light absorption in the crystal, which can be obtained by calculating the momentum matrix elements between the occupied and the unoccupied states [26], obeying the selection rule. Then, the real part of the dielectric function, ε 1 (ω), governs the propagation behaviour of electromagnetic field in a material, is derived from the imaginary part using the Kramers-Kronig transformation [27].…”
Section: X= Sn Ti and Zr)mentioning
confidence: 99%
“…5, wavelength of tangent of transmittance upheaval place was at about 367-375 nm, indicating that characteristics of wavelength was¯rst blue shift and then red shift. A detailed research about the variations in the optical properties, bandgap, and nonlinear behavior of the compound with the change in the Ga doping concentration was carried out by Amin 14 and Maqbool. 17 The above conclusion was similar to Dai Jielin's, 18 who prepared ZnO thin¯lms with doping In.…”
Section: Transmittance Analysismentioning
confidence: 99%